Interaction Creates Learning: Engaging Learners with Special Educational Needs through Orff-Schulwerk - Markku Kaikkonen; Sanna Kivijärvi (Approaches: Music Therapy & Special Music Education, 2013)
We consider the individual and the collective as fundamentally interdependent. Interaction leads to learning and therefore theories of interaction are of importance. For a music teacher, the achieved awareness can lead to practical advances. Discovering the most productive interactional strategy and understanding the consequences of actions within the actual learning situation can be helpful in creating interaction and learning. However, as interaction is dynamic and complex, especially those practitioners working with students with Special Educational Needs (SEN) may not be satisfied with the respective conceptual frameworks on interaction processes.